Mithramycin A and Mithralog EC-8042 inhibit SETDB1 expression and its oncogenic activity in malignant melanoma - Federico, Aniello; Steinfass, Tamara; Larribere, Lionel; Novak, Daniel; Morís, Francisco; Núñez, Luz-Elena; Umansky, Viktor; Utikal, Jochen (Molecular therapy. Oncolytics, 2020)
Malignant melanoma is the most deadly skin cancer, associated with rising incidence and mortality rates. Most of the patients with melanoma, treated with current targeted therapies, develop a drug resistance, causing tumor relapse. The attainment of a better understanding of novel cancer-promoting molecular mechanisms driving melanoma progression is essential for the development of more effective targeted therapeutic approaches. Recent studies, including the research previously conducted in our laboratory, reported that the histone methyltransferase SETDB1 contributes to melanoma pathogenesis. In this follow-up study, we further elucidated the role of SETDB1 in melanoma, showing that SETDB1 modulated relevant transcriptomic effects in melanoma, in particular, as activator of cancer-related secreted (CRS) factors and as repressor of melanocyte-lineage differentiation (MLD) and metabolic enzymes. Next, we investigated the effects of SETDB1 inhibition via compounds belonging to the mithramycin family, mithramycin A and mithramycin analog (mithralog) EC-8042: melanoma cells showed strong sensitivity to these drugs, which effectively suppressed the expression of SETDB1 and induced changes at the transcriptomic, morphological, and functional level. Moreover, SETDB1 inhibitors enhanced the efficacy of mitogen-activated protein kinase (MAPK) inhibitor-based therapies against melanoma. Taken together, this work highlights the key regulatory role of SETDB1 in melanoma and supports the development of SETDB1-targeting therapeutic strategies for the treatment of melanoma patients.